PRACTICAL ISOLATION OF BULLATACIN FROM ANNONA MURICATA LEAVES AND QUANTITATIVE ANALYSIS OF ACETOGENINS AS TOTAL LACTONES - K. MULIA; S.W. WINARCAHYO (International Journal of Pharma and Bio Sciences, 2013)
Annonaceous Acetogenins Are Bioactive Compounds Present In The Leaves Of Annona Muricata (Soursop) With Significant Anti-Cancer Activities. In This Study, Acetogenin-Rich Methanol Fraction Extracted From Soursop Leaves Was Further Fractionated And Isolated Using A Simple Open Column Chromatography Technique With Silica Gel As The Stationary Phase. Eluted Fractions Rich In Acetogenin Compounds Were Identified Using The Kedde Reagent Which Formed A Distinctive Red-Pink With The Unsaturated g-Lactone Group Present In All Of Acetogenin Compounds. Liquid Chromatography Analysis Showed That Pure Bullatacin Was Obtained. The Isolated Bullatacin, Combined With Andrographolide, Were Used As Standards In The Visible Spectrophotometry For Quantitative Analysis Of Acetogenin. It Is Shown That Andrographolide Could Be Used For Quantitative Analysis Of Acetogenins Using Visible Spectrophotometry, As An Alternative To Liquid Chromatography Analysis That Requires Pure Acetogenin Which Is Not Available Commercially. The Amount Of Total Acetogenins In The Methanol Extract Of Soursop Leaves, Measured As Total Lactones, Reached As Much As 22%-Weight.